Impact of particle chemical composition and water content on the photolytic reduction of particle-bound mercury. (1st March 2019) - Deng, Chunyan; Tong, Yindong; Chen, Long; Yuan, Wen; Sun, Yingli; Li, Jinling; Wang, Xuejun; Zhang, Wei; Lin, Huiming; Xie, Han; Bu, Xiaoge
Abstract: The current understanding of Hg(II) photolytic reduction in atmospheric particles is inadequate. This study addresses the impacts of the particle chemical composition (e.g. anions, trace elements, and carbon concentrations) and water content on the Hg(II) photolytic reduction process under ambient conditions. The results showed that Hg(II) in particles was significantly reduced under irradiation and this process could be prohibited by certain heavy metals and promoted by increasing water content in particles. Negligible evolved Hg(0) amount was observed from particles under dark condition (occupying for <0.5% in particle-bound mercury). With a 10% increase in water content, the corresponding Hg(II) reduction rate increased by 1–5% after 30 min of light exposure (at an irradiance of 1000 W/m 2 ). The Hg(II) photolytic reduction in particles generally correlates with first-order reaction kinetics, with a half-life in a clear sky of 1.6 and 12.2 h for particles collected in the summer and winter, respectively. This study demonstrates that Hg(0) evolves quickly under light exposure regardless of whether the particles are wet or dry, and these processes need to be specified in future atmospheric Hg modelling. Graphical abstract: Highlights: Impacts of the particle chemical composition and water content on Hg(II) photolytic reduction were studied. Hg(II) in particles was significantly reduced under irradiation, but could be prohibited by some heavy metals. Water contents in the particles could promote the Hg(II) reduction process. Hg(II) reduction processes should be updated in future atmospheric Hg modelling.